PENGARUH PELATIHAN DAN PENEMPATAN TERHADAP MOTIVASI SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA BATANG HARI JAMBI - Arna Suryani; Rahma Linda (J-MAS (Jurnal Manajemen dan Sains), 2017)
The purpose of this study was to determine (1) an overview of the training , placement  motivation  and performance  employees at the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. (2) the effect of training  and placement  on the motivation  employees at the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. (3) the effect of training  and placement  on the performance  employees at the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. (4) the effect of motivation  on the performance  employees at the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. (5) the effect of training  and placement  through motivation  on the performance  employees of the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. Object of research is Regional water company (PDAM)  Tirta Batang Hari, jambi. this company of handling water treatment at regional Batang Hari province jambi .this company producted oriented product public service at regional Batang Hari province jambi. total population at administration Batang Hari years 2014 approximately 305.115 persons, service area total population 114.424 persons, include 12 villages. Consumers had serviced 37.608 people. Costumers of this company one of 5.597 houses, 329 busineses, 116 government instations, 74 socials, 1 hotel. This research is descriptive and verification. The population in this study are employees of the Regional Water Company (PDAM) Tirta Batang Hari, Jambi. This study uses a whole number of employees as many as 59 people pegawai..Data analyzed using two (2) ways, namely (1) Using path analysis (path analysis). to determine the factors that influence employee performance by t test and F test at the significance level (α = 0.05), (2) Using the coefficient of determination to determine the factors that influence employee performance with simultaneous determination coefficient value (R2) and partial (r2). Results of research coefficient of determination (R2) the effect of training (X1) placement (X2) on the motivation (Y) amounted to 29.3%, and the coefficient of determination (R2) the effect of training (X1) placement (X2) on the performance (Z) by 40 , 4%. For the coefficient of determination (R2) the influence of motivation (Y) on the performance (Z) of 38.7%. Conclusions from the study showed, descriptively average for the variable Training (X1) placement (X2) Motivation (Y) employee performance (Z) of 1893.8, which means in the category "Strongly Agree". And for verification analysis research all these variables showed a significant influence on the motivation and performance of employees Regional Water Company (PDAM) Tirta Batang Hari, Jambi.Keywords: Training, Placement, Motivation, Employee Performance